Endoscopic submucosal dissection for early gastric cancer: a large-scale feasibility study. Issue 3 (10th November 2008) - Isomoto, H; Shikuwa, S; Yamaguchi, N; Fukuda, E; Ikeda, K; Nishiyama, H; Ohnita, K; Mizuta, Y; Shiozawa, J; Kohno, S
Abstract : Objective: Endoscopic submucosal dissection (ESD) has the advantage over conventional endoscopic mucosa resection, permitting removal of early gastric cancer (EGC) en bloc, but long-term clinical outcomes remain unknown. A follow-up study on tumour recurrence and survival after ESD was conducted. Method: ESD was performed for patients with EGC that fulfilled the expanded criteria: mucosal cancer without ulcer findings irrespective of tumour size; mucosal cancer with ulcer findings ⩽3 cm in diameter; and minute submucosal invasive cancer ⩽3 cm in size. 551 patients with 589 EGC lesions were enrolled. The patients underwent ESD and then received periodic endoscopic follow-up and metastatic surveys for 6–89 months (median, 30 months). The main outcome measures were resectability (en bloc or piecemeal resection), and curability (curative or non-curative). Complications were assessed, and factors related to each were analysed statistically. The overall and disease-free survival rates were estimated. Results: En bloc resection was achieved in 94.9% (559/589), and larger lesions were at higher risk of piecemeal resection. 550 of 581 lesions (94.7%) were deemed to have undergone curative resection. En bloc resection was the only significant contributor to curative ESD. Patients with non-curative resection developed local recurrence more frequently. The 5-year overall and disease-specific survival rates were 97.1% and 100%, respectively. Conclusion: Precise assessment of curability with successful one-piece resection may reduce tumour recurrence after ESD. The prognosis of EGC patients treated by ESD is likely to be excellent, though further longer follow-up studies are warranted.